Illusion of Control and the Pursuit of Authority - Randolph Sloof; Ferdinand von Siemens (Center for Economic Studies and ifo Institute (CESifo), 2014)
In a laboratory experiment, we measure subjects' willingness to pay for a transparently useless decision right concerning the choice between two real effort tasks. We also elicit for each participant her change in beliefs about the likelihood of receiving her preferred task if she rather than another participant makes the decision. Participants pay more to keep control if they - irrationally - believe that they can increase the probability of getting their preferred task by keeping control. We thus document that illusion of control exists in a controlled environment with monetary incentives, and that illusion of control might affect people's pursuit of authority.
Keywords: C91; D23; D80; 330; control preferences; illusion of control; allocation of decision rights